Reward Promotes Self-Face Processing: An Event-Related Potential Study - Zhan, Youlong; Chen, Jie; Xiao, Xiao; Li, Jin; Yang, Zilu; Fan, Wei; Zhong, Yiping (Frontiers in Psychology, 2016)
The present study adopted a reward-priming paradigm to investigate whether and how monetary reward cues affected self-face processing. Event-related potentials (ERPs) were recorded during judgments of head orientation of target faces (self, friend, and stranger), with performance associated with a monetary reward. The results showed self-faces elicited larger N2 mean amplitudes than other-faces, and mean N2 amplitudes increased after monetary reward as compared with no reward cue. Moreover, an interac-tion effect between cue type and face type was observed for the P3 component, sug-gesting that both self-faces and friend-faces elicited larger P3 mean amplitudes than stranger-faces after no reward cue, with no significant difference between self-faces and friend-faces under this condition. However, self-faces elicited larger P3 mean ampli-tudes than friend-faces when monetary reward cues were provided. Interestingly, the enhancement of reward on friend-faces processing was observed at LPP (450-600 ms), suggesting that the LPP difference between friend-faces and stranger-faces was en-hanced with monetary reward cues. Thus, we found that the enhancement effect of re-ward on self-relevant processing occurred at the later stages, but not at the early stage. These findings suggest that the activation of the reward expectations can enhance self-face processing, yielding a robust and sustained modulation over their overlapped brain areas where reward and self-relevant processing mechanisms may operate together.